2010
DOI: 10.2176/nmc.50.330
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Sinus Cavernous Hemangioma Largely Extending Into the Sella Turcica and Mimicking Pituitary Adenoma -Case Report-

Abstract: A 77-year-old female presented with a rare cavernous sinus cavernous hemangioma with extension to the sella turcica, neuroradiologically mimicking nonfunctioning pituitary macroadenoma. The lesion was partially removed via transsphenoidal surgery, and the histological diagnosis was cavernous hemangioma. After stereotactic radiosurgery using a cyber knife, the lesion decreased in size. Stereotactic radiosurgery may be a good option for cavernous sinus cavernous hemangioma with high risk of surgical bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
1
14
0
3
Order By: Relevance
“…According to some published reports, the lesions are quite radiosensitive; radiosurgery and conventional radiotherapy should therefore be important in overall management [21][22][23][24][25]. Several reports in the literature have demonstrated that radiosurgery can be used with high lesion control [7][8][9][10][11][12][13][14][15][16]. Meta-analysis of the published literature suggests that stereotactic radiosurgery seems to provide satisfactory tumor control with little risk, at least over the published follow-up periods reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to some published reports, the lesions are quite radiosensitive; radiosurgery and conventional radiotherapy should therefore be important in overall management [21][22][23][24][25]. Several reports in the literature have demonstrated that radiosurgery can be used with high lesion control [7][8][9][10][11][12][13][14][15][16]. Meta-analysis of the published literature suggests that stereotactic radiosurgery seems to provide satisfactory tumor control with little risk, at least over the published follow-up periods reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkable tumor shrinkage was demonstrated in 39 (70.9%) of 55 patients and the mean radiation dose received was 14 Gy (range [10][11][12][13][14][15][16][17][18][19]. The mean radiation dose received by 16 patients with partial or no change tumor shrinkage was 13.5 Gy (range [10][11][12][13][14][15][16]. Patients with remarkable tumor shrinkage (volume reduction rates of C50% relative to those before stereotactic radiosurgery) received higher doses than those with partial tumor shrinkage or no change (P = 0.031).…”
Section: Dose and Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of cavernous hemangioma is low, but due to the possibility of hemorrhage or neurological abnormalities, the risk cannot be underestimated. Intrasellar cavernous hemangioma is a particularly rare disease; there were only seven previous cases reported overseas and only one prior case reported in Korea; each of these cases is presented in Table 3 [12,13,14,15,16,17,18,19]. Intrasellar or cranial cavernous hemangioma was introduced by Lombardi et al [12] in 1994, and was classified into three types: hemangioma of the cavernous venous sinus growing lateral or medial to the lumen of the venous sinus, or growing outside of the cavernous venous sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial extracerebral (i.e. extra-axial) cavernous malformations (ECCMs) are rare and comprise 0.4 to 2% of all intracranial cavernous malformations 1,3 . ECCMs usually arise in relation to the dura mater.…”
Section: Introductionmentioning
confidence: 99%